From the Restructuring of the Power Sector to Diversification of Renewable Energy Sources: Preconditions for Efficient and Sustainable Electricity Market - CeroviÄ‡, Ljerka; Maradin, Dario; ÄŒegar, SaÅ¡a (International Journal of Energy Economics and Policy, 2014)
Efficient and well-developed power sector enables growth and boost of the economy, competitiveness of the national economy, affects the improvement of living standard of the population and development of society. In this respect, the basic task of the power sector is to ensure quality delivery of electricity to consumers that is secure and reliable, with optimal price of electricity and acceptable dynamics of delivery. Since the beginning of the 1980s until present time, the electric power sector has been facing a series of reforms and related restructuring processes aiming to improve the efficiency of the electricity market. This implies liberalisation and privatisation, and unbundling of power activities by which market competition is introduced in the production and supply of electricity. In the process of developing the power sector, it is necessary that the interests of preserving the environment for future generations are equally important as economic and energy interests of today’s generations. In this regard, it is environmentally and economically justified to base the development of power systems on renewable energy sources. Increasing the share of renewable energy sources in the national electricity systems will contribute to an increase in energy and environmental efficiency in production and distribution of electricity and, consequently, energy sustainability of national economies. Keywords: power sector restructuring; diversification of RES; efficiency; sustainability; environment JEL Classifications: D24; Q42; Q56